Clinical Evaluation of Apex Locators and Cone-Beam Computed Tomographic for Working Length Determination in Pulp Canal Obliterated Traumatized Maxillary Incisors - I Anand Sherwood; Lucila Piasecki; Pavula S; Pradeepa MR; Divyameena B; Nivedha V; Ramyadharshini T; Valliapan CT (Journal of Orofacial Research, 2021)
Aim: This clinical study evaluated pre- and intra-operative working length (WL) determination in incisors presenting with pulp canal obliteration (PCO), with cone beam computed tomography (CBCT) images measured by three softwares (3D Endo, SICAT and Horos), five electronic apex locators (EALs) (Apex ID, Canal Pro, E-Pex Pro, iPex II, and Root ZX Mini), and periapical radiographs. Materials and Methods: 24 maxillary incisors with history of trauma and PCO were included. Pre-operative CBCT WL measurements were performed using the softwares. Five EALs according to manufacturer’s instructions, followed by the radiographic method. Results: Pre-operative CBCT measurements (n=16) were similar among the different software (P>.05). Radiographic WL strongly correlated with CBCT measurements (P<.001). Multiple regression analysis showed significant association between all the pre and intra-operative WL methods (P<.001). Conclusions: EAL measurements were adequate regardless the type of device, but restricted to the cases presenting foraminal patency. CBCT measurements might be useful for working length determination in PCO incisors.